Conditional QTL mapping of three yield components in common wheat (Triticum aestivum L.) - Han Zhang (Crop Journal, 2016)
Spike number per m2 (SN), kernel number per spike (KNPS) and thousand-kernel weight (TKW) are the three main components determining wheat (Triticum aestivum L.) yield. To evaluate the relationships among them a doubled haploid (DH) population consisting of 168 lines grown at three locations for three years was analyzed by unconditional and conditional QTL mapping. Thirty-three unconditional QTL and fifty-nine conditional QTL were detected. Among them, two QTL (QSN-DH-2B and QSN-DH-3A-1.1) improved SN, with no effect on KNPS. QKNPS-DH-2B-2.1 improved KNPS, with no effect on SN. QKNPS-DH-1A-1.1, QKNPS-DH-2D-1.1 and QKNPS-DH-6A improved KNPS, with no effect on SN or TKW. QKNPS-DH-6B was associated with increased SN and TKW. In addition, QTKW-DH-4B, QTKW-DH-5B and QTKW-DH-7B increased TKW without decreasing KNPS. These results provide useful information for marker assisted selection (MAS) and improvement in wheat yield.